Case Report: Severe vitamin D deficiency in a girl with inflammatory myopathy and myonecrosis - Kanouse, Andrew; Nwosu, Benjamin Udoka; Salemi, Parissa (Frontiers in Pediatrics, 2024)
Inflammatory myopathies are a rare group of disorders that can cause significant disruption of an individual's ability to adequately perform activities of daily living. We present a case of a child presenting with substantial compromise of her ambulation with a muscle biopsy consistent with myonecrosis. She was subsequently diagnosed with an inflammatory myopathy and started on glucocorticoid and methotrexate therapy with minimal symptomatic improvement. Further in her clinical course, hypocalcemia and an undetectable 25-hydroxyvitamin D level were found.Prompt institution of calcium and vitamin D supplementation significantly improved her myopathy. While there is literature linking vitamin D deficiency with myopathy, there is a lack of data on the association between hypocalcemia or vitamin D deficiency with myonecrosis, which could represent comorbid states in myonecrosis. Therefore, vitamin D status should be established in all patients with myonecrosis, as vitamin D deficiency is easy to diagnose and treat, and our case shows that such treatment could lead to significant clinical improvement.